Drinking Water Security in the Mid-hill Region of Nepal - Durga D. Poudel; Timothy W. Duex; Roshan Poudel (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2020)
Drinking water security is increasingly becoming a global concern in recent decades. The mid-hill region of Nepal is also experiencing serious water shortages in recent years. In order to assess the availability of drinking water in the mid-hill regions of Nepal, we studied hydrogeology, land use types and collected water samples from 30 springs in Kavre, Kahmandu Valley, Nuwakot and Tanahu in Nepal between July 17-September 12, 2017. For each sampling spring, while surrounding land use type (mixed, agriculture, urban, vegetation) and spring type (fracture, depression, contact) were determined through field observation, the field pH, conductivity and temperature was determined using relevant probes and thermometers. Water samples were collected in 1L and 165mL plastic bottles for chemical and total coliform determination, respectively, in the lab. Bottles were rinsed twice using spring water before filling them with sample water, then stored in an ice chest, and brought to the lab. In the laboratory, turbidity, conductivity, Ca, Mg, HCO3, SO4, Na, NO3, Cl, Fe, As, and total coliform were determined using standard methods. Spring water in agricultural areas showed significantly higher suspended solids compared to other land use types whereas spring water in urban areas showed significantly higher dissolved substances. By spring type, turbidity and conductivity values and the concentration of dissolved constituents (Ca, Mg, HCO3, SO4, NO3, and Cl) were ranked in the order of fracture < contact < depression. Na and Fe concentration were in the order of fracture = contact < depression. By land-use type, conductivity and dissolved constituents (Ca, Mg, HCO3) were in the order of agriculture < vegetation < mixed < urban. Whereas urban land use had the highest values for SO4, Na, NO3, and Cl, other land use types showed variable order. Fe concentration was ranked in the order of urban < mixed < vegetation < agriculture. Total coliform was in the order of mixed < agriculture < urban < vegetation. These results indicate that land use type and surface condition, which is possibly associated with human activities, heavily affect spring water properties in the region. These results suggest that drinking water security of mid-hill region of Nepal is threatened heavily due to poor spring water quality. Protection of drinking water sources should be specific to land use type and activities around the springs. Index Terms— three to six pertinent, specific to the paper, keywords added after the abstract, separated by commas.